Rupture of Intracranial Aneurism in Medicolegal Autopsies - Akyıldız, Elif Ülker; Şenel, Berna; Ersoy, Gökhan; Pakiş, Işıl; Karayel, Ferah; Turan, Arzu Akçay; Çelik, Safa (The Bulletin of Legal Medicine, 2005)
Subarachnoid hemorrhage, due to rupture of an intracranial aneurysm, is a serious condition with high mortality and morbidity rates. A significant portion of patients with aneurysmal subarachnoid hemorrhage die immediately before reaching the hospital. The authors reviewed 12 medicolegal autopsies in which the cause of death was ruptured cerebral artery aneurysm. There were 6 women and 6 men with a mean age of 41.4 years. Of these 12 patients, 8 died without reaching medical attention. At autopsy, subarachnoid hemorrhage was present in 10 patients (91%), and intracerebral hemorrhage was present in one patient. Ten patients (83%) had acute pulmonary edema. There was no connection of the ruptures with a physical trauma. Autopsy and dissection of the cerebral vessels is vital to diagnosis, particularly when deaths are sudden and unexpected in nature.Key words: Aneurism, cranial, rupture, autopsy
Keywords: aneurism; cranial; rupture; autopsy